Damage mechanisms in an EB-PVD thermal barrier coating system during TMF and TGMF testing conditions under combustion environment. (June 2017) - Mauget, Florent; Hamon, Florence; Morisset, Médéric; Cormier, Jonathan; Riallant, Fanny; Mendez, José
Highlights: Durability of a EB-PVD TBC system during Out-of-Phase (OP) TMF. OP TMF in simulated combustion environment. Decrease of the OP-TMF life with a degradation of the γ/γ′ microstructure. Superimposing an through thickness thermal gradient increase the TMF life. A prior thermal aging could increase the time to spallation of the top coat. Abstract: Modern high pressure turbine blades and vanes of aero-engines are cooled and thermally protected using a thermal barrier coating (TBC) system. TBC systems are submitted to very complex service loadings, with a combination of mechanical and thermal fatigue under complex thermal gradients, in addition to the contribution of oxidation to the damage processes. The high temperature durability under combustion environment of the AM1/NiAlPt/EB-PVD TBC system used for high temperature blades and vanes has been investigated performing out of phase load-controlled thermo-mechanical fatigue (TMF) and thermal-gradient-mechanical fatigue (TGMF) tests in the 500–1100 °C temperature range. This characterization has been performed using the MAATRE burner where massive or hollow samples can be mechanically loaded under hot gas flow conditions. This unique test rig allows for gas testing temperatures up to 1600 °C and internal cooling of hollow samples. The damage mechanisms under different TMF conditions are presented and the impact of a through thickness thermal gradient (induced by means of internal cooling) is analyzed. Moreover, a prior thermal over-aging of the whole system is investigated to mimic service degradation. It is shown in this work that depending on the tensile stress applied at low temperature, a change in the main degradation mechanism of the TBC system is observed. Moreover, the thermal over-aging before TMF tests favors cycling ratcheting in compression during thermo-mechanical cycling due to the degradation of the substrate microstructure.